Empowering Pregnant Women in Choosing Postpartum Contraception Using Digital Booklet - Nilakesum, Nur Fadjri; Susilawati, Dewi; Yusnela, Eza; Lisa Rahmadani; Mageretta, Serli; Permata, Citra Intan; Massagus, Zharfa Adani (Jurnal Abmas Negeri (JAGRI), 2025)
The rate of postpartum contraceptive use remained relatively low. Based on data from BKKBN, only around 36% of mothers used postpartum contraception. The low utilization of Postpartum Family Planning (PFP) increased the risk of closely spaced pregnancies, which contributed to high maternal and infant mortality rates (MMR and IMR). PFP played a significant role in reducing MMR and stunting. In 2022, according to Senior Expert of the Presidential Staff Office, Dr. Brian Sri Prahastuti, the achievement of PFP was only around 35,78% of the 40% target. Various factors influenced the low acceptance of postpartum contraceptives, with lack of knowledge being one of the primary causes. This lack of knowledge and family support was also due to the limited dissemination of information, resulting in pregnant women and their families being unaware of the importance of PFP. This activity aimed to promote PFP by empowering pregnant women through the use of a digital booklet. The implementation followed five stages: planning, action, observation, evaluation, and reflection. The activity was conducted on November 19, 2024, in the pregnant women’s class at TPMB Nomretti. The results showed an increase in maternal knowledge after counseling through a Focus Group Discussion (FGD) using the digital booklet, with average knowledge scores increasing from 4,9 to 8,9. In addition, five out of eight pregnant women stated that they intended to use PFP, two with IUDs and three with implants. In conclusion, PFP achievement could be improved if counseling was provided to pregnant women using engaging educational media.